2020
DOI: 10.1038/s41598-020-57966-z
|View full text |Cite
|
Sign up to set email alerts
|

Biosynaptic devices based on chicken egg albumen:graphene quantum dot nanocomposites

Abstract: Biosynaptic devices based on chicken egg albumen (ceA):graphene quantum dot (GQD) hybrid nanocomposites were fabricated to achieve stable synaptic behaviors. current-voltage (i-V) curves for the biosynaptic devices under consecutive negative and positive voltage sweeps showed clockwise pinched hysteresis, which is a critical feature of a biological synapse. The effect of the GQD concentration in the ceA layer on the device performance was studied. the retention time of the biosynaptic devices was relatively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Wang controlled the current switching ratio of Al/graphene oxide (GO)/EA/GO/ITO devices using varying concentrations of GO [ 18 ]. Other studies have demonstrated that RRAMs made from egg proteins are water soluble [ 19 ], can successfully simulate the memory behaviour of biological synapses [ 20 , 21 , 22 ], can be flexibly transferred to many unconventional substrates [ 23 ], and can realize the full memory logic block of the non-gate, or-gate, and and-gate [ 24 ]. Egg proteins can also be made into gate dielectric layers of organic field effect transistors and other transistors [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang controlled the current switching ratio of Al/graphene oxide (GO)/EA/GO/ITO devices using varying concentrations of GO [ 18 ]. Other studies have demonstrated that RRAMs made from egg proteins are water soluble [ 19 ], can successfully simulate the memory behaviour of biological synapses [ 20 , 21 , 22 ], can be flexibly transferred to many unconventional substrates [ 23 ], and can realize the full memory logic block of the non-gate, or-gate, and and-gate [ 24 ]. Egg proteins can also be made into gate dielectric layers of organic field effect transistors and other transistors [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…An artificial synapse device based on chicken EA, graphene QD nanocomposites, was reported recently. [ 155 ] The conductance gradually decreased in consecutive positive and negative voltage sweeping, indicative of the ability to mimic synaptic plasticity. However, the conductance can't be modulated to a higher level according to the experiment results, which would limit its emulation of PPF.…”
Section: Protein‐based Electronics For Brain‐inspired Computingmentioning
confidence: 99%
“…Egg albumen has been employed to develop memristor devices due to its easy extraction, high transparency, easy processing, low cost, and excellent dielectric properties. [18][19][20][21][22][23] Wherein, melanin/glycerin, [22] Au@SiO 2 core-shell nanoparticles, [20] graphene quantum dots, [21] and H 2 O 2 [23] were used to modify the egg albumen to obtain better resistive switching performances. Meanwhile, Other protein-based materials were also employed by delicately controlling the dynamics of defects, [24] functional groups, [25] and metallic atoms [26,27] to induce gradual conductance changes.…”
Section: Introductionmentioning
confidence: 99%